N-Heterocyclic Carbenes: Molecular Porters of Surface Mounted Ru-Porphyrins - Knecht, Peter; Meier, Dennis; Reichert, Joachim; Duncan, David A.; Schwarz, Martin; Küchle, Johannes T.; Lee, Tien-Lin; Deimel, Peter S.; Feulner, Peter; Allegretti, Francesco; Auwärter, Willi; Médard, Guillaume; et al. (Angewandte Chemie - International Edition, 2022)
Abstract Ru-porphyrins act as convenient pedestals for the assembly of N-heterocyclic carbenes (NHCs) on solid surfaces. Upon deposition of a simple NHC ligand on a close packed Ru-porphyrin monolayer, an extraordinary phenomenon can be observed: Ru-porphyrin molecules are transferred from the silver surface to the next molecular layer. We have investigated the structural features and dynamics of this portering process and analysed the associated binding strengths and work function changes. A rearrangement of the molecular layer is induced by the NHC uptake: the NHC selective binding to the Ru causes the ejection of whole porphyrin molecules from the molecular layer on silver to the layer on top. This reorganisation can be reversed by thermally induced desorption of the NHC ligand. We anticipate that the understanding of such mass transport processes will have crucial implications for the functionalisation of surfaces with carbenes.
Keywords: Metalloporphyrins; N-Heterocyclic Carbenes; scanning tunnelling microscopy; Surface Chemistry; X-Ray Standing Waves